ANALISIS TEKNOLOGI HIJAU, PENGARUH SOSIAL, DAN KUALITAS KEHIDUPAN KERJA TERHADAP KEPUASAN KERJA PADA INDUSTRI SERAT KREATIF DI INDONESIA - Handa Ardiko; Tri Darsono (Universitas Mercu Buana Yogyakarta, 2025)
The management of human resources based on Green Human Resource Management (GHRM) plays a crucial role in supporting an organization’s sustainable development strategy. Human resources must be aligned with sustainable development planning, environmentally friendly regulations, and a workplace culture that promotes sustainability. The main objective of this study is to analyze the influence of green technology, social influence, and quality of work life on employee job satisfaction in the creative fiber industry in the Special Region of Yogyakarta, Indonesia.To achieve this objective, the research sample consisted of 159 employees from creative fiber industries in Yogyakarta who apply environmentally friendly technologies. Samples were determined using the Slovin formula, and data were collected through random sampling and double sampling methods. A total of 16 indicators from four variables were measured using a Likert scale. Data analysis included validity and reliability testing as well as Variance-Based Structural Equation Modeling (SEM) using SmartPLS version 4. The results show that quality of work life does not have a significant effect on employee job satisfaction in the creative fiber industry in Yogyakarta. However, green technology and social influence have a significant positive effect on job satisfaction. Theoretically and practically, these findings provide insights for organizations to enhance the quality of work life through a better balance between employee needs and job demands, training programs, and supportive work environments. Such efforts are expected to improve productivity, employee loyalty, well-being, and overall organizational performance.